Energetic and exergetic study for cross-corrugated membrane-based total recovery exchanger for ventilation - Abduljabbar, Ahmed A. (Cranfield University, 2017)
Indoor air quality is an important component of the air conditioning of buildings due to its major effect on the health of the occupants, thus the air supplied to these buildings by the ventilation system should be sufficient, clean and healthy. A most promising development was the heat recovery system which offers better thermal energy efficiency and comfort with adequate fresh air. An energetic and exergetic analysis has been conducted on a cross-corrugated membrane based total heat exchanger core for ventilation of single dwellings. In order to enhance the sensible and latent effectiveness of the heat and mass transfer intensification was achieved by selecting Polyethersulfone for the membrane material, and a cross-corrugation arrangement of different dimensions for the primary surface exchanger. The design was tested against a ventilation air volume flow rate for an individual household; from 85 to 100 m³/hr. The dimensions of the exchanger were based on the polymer core being developed by Redring-Xpelair, Peterborough UK, with core dimensions of width and length both 250 mm, and a range of heights 100 – 500 mm. The cross-corrugated design of the test core had triangular openings with pitch lengths of 5, 10 and 25 mm. The ambient conditions were for a cold and humid winter in the UK. The ambient temperature test values were 2, 4, 6, 8 and 10 °C, and the inlet air velocities in the core were 0.5, 1.0, 1.5 and 2 m/s, with Reynolds numbers not exceeding 2200. CFD studies were conducted to investigate the thermal-fluid performance of the core, the Transition-SST model was used in the simulations within ANSYS Fluent 17.1 software and was validated using experimental data in the literature. The proposed model performed successfully in this study and proved that it was compatible with the test conditions. The exergetic analysis was conducted using the IPSEpro modelling software, by creating a system consisting of membrane core, a domestic dwelling, fresh air and exhaust fans. The energetic analysis results were the basis of the IPSEpro modelling to determine the exergy, the exergetic efficiency and exergy destruction in the system. The study concluded from both the energetic and the exergetic analysis that the membrane based exchanger core showed promising performance as a total heat and moisture recovery application with sensible and latent effectiveness values varying from 65% to 82%; and exergetic efficiency values varying from 30% to 60%, depending on core geometry and ambient conditions. The chemical exergy was the dominant factor in the performance in all cases, and the membrane core had the highest exergy destruction percentage comparing to the other system components. Decreasing the pitch length of the exchanger core intensified its performance, the 5 mm case showed the best performance, but there are likely to be difficulties in manufacturing such a compact core. But, and more directly, its use would mean unpleasant compromises due to the extremely higher pressure drop across such a core even at low Reynolds numbers. The 10 mm case gave a better performance than the 25 mm, but not substantially different, therefore, the optimum choice lies between the better heat and mass transfer performance of the 10 mm case and the lower pressure drop and relative ease of manufacture of the 25 mm.